J/ψ production at midrapidity in p-Pb collisions at s NN $$ \sqrt{s_{NN}} $$ = 8.16 TeV - The ALICE collaboration; S. Acharya; D. Adamová; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S. U. Ahn; I. Ahuja; A. Akindinov; et al. (Journal of High Energy Physics, 2023)
Abstract The production of inclusive, prompt and non-prompt J/ψ was studied for the first time at midrapidity (−1.37 < y cms < 0.43) in p-Pb collisions at s NN $$ \sqrt{s_{NN}} $$ = 8.16 TeV with the ALICE detector at the LHC. The inclusive J/ψ mesons were reconstructed in the dielectron decay channel in the transverse momentum (p T) interval 0 < p T < 14 GeV/c and the prompt and non-prompt contributions were separated on a statistical basis for p T > 2 GeV/c. The study of the J/ψ mesons in the dielectron channel used for the first time in ALICE online single-electron triggers from the Transition Radiation Detector, providing a data sample corresponding to an integrated luminosity of 689 ± 13 μb −1. The proton-proton reference cross section for inclusive J/ψ was obtained based on interpolations of measured data at different centre-of-mass energies and a universal function describing the p T-differential J/ψ production cross sections. The p T-differential nuclear modification factors R pPb of inclusive, prompt, and non-prompt J/ψ are consistent with unity and described by theoretical models implementing only nuclear shadowing.